The influence of selected risk factors on the hearing threshold level of noise exposed employees - DUDAREWICZ, Adam; TOPPILA, Esko; PAWLACZYK-ŁUSZCZYŃSKA, Małgorzata; ŚLIWIŃSKA-KOWALSKA, Mariola (Archives of Acoustics, 2010)
The aim of the study was to evaluate the combined effect of noise exposure and additional risk factors on permanent hearing threshold shift. Three additional risk factors were: exposure to organic solvents, smoking and elevated blood pressure.The data on exposure and health status of employees were collected in 24 factories. The study group comprised of 3741 noise male exposed workers of: mean age 39±8 years, mean tenure 16±7 years and LEX,8h=86±5 dB. For each subject, hearing level was measured with pure tone audiometry, blood pressure and noise exposure were assessed from the records of local occupational health care and obligatory noise measurements performed by employers. Smoking and solvent exposure were assessed with questionnaire. The study group was divided into subgroups with respect to the considered risk factors. In the analysis, the distribution of hearing level of each subgroup was compared to the predicted one which the standard calculation method described in ISO 1999:1990. For each of the considered risk factors, the difference between measured and calculated hearing level distribution was used to establish, by the least square method, a noise dose related correction square function for the standard method. The considered risk factors: solvent exposure, smoking and elevated blood pressure combined with noise exposure, may increase degree of hearing loss.